Health and reproductive experiences of women with an FMR1 premutation with and without fragile X premature ovarian insufficiency - Wheeler, Anne C.; Raspa, Melissa; Green, Annette; Bishop, Ellen; Bann, Carla; Edwards, Anne; Bailey, Donald B. (Frontiers in Genetics, 2014)
Recently, research has indicated an increased risk for greater medical and emotional comorbidity and physical health symptoms among women with an FMR1 expansion. However, these studies have generally been limited in their ability to model multiple risk factors associated with these symptoms by small numbers (n = 112 to 146) of participants. This study used survey methodology to examine the health experiences of 458 adult women with the premutation with and without a history of an FXPOI diagnosis. Results suggest similar findings to those reported in the literature with regard to the frequency of medical, emotional, and reproductive experiences of women with the premutation. In addition to expected reproductive differences, women with a diagnosis of FXPOI were also more likely to experience dizziness, nausea, and muscle weakness than women without a diagnosis of FXPOI. Women with and without FXPOI were more likely to have used reproductive assistance and were more likely to have experienced preeclampsia during at least one pregnancy than is reported in the general population. Having comorbid depression and anxiety was predictive of increased medical conditions and increased daily physical health symptoms.